Breast cancer stem cells - Rydhed, Erica (2011)
This literature study aims to examine the existence of cancer stem cells in breast cancer. The cancer stem cell theory states that there is a hierarchical organization within a tumour, in which a small subpopulation of the cells can initiate new tumours and maintain tumour growth whilst the bulk of the tumour cannot. These tumour initiating cells have shown to possess many characteristics similar to those of adult stem cells, which is why they are often referred to as cancer stem cells. Both cell types have the capacity of asymmetric division and have shown to possess mechanisms of resistance to both apoptosis and cancer drugs. The cancer stem cell theory elucidates many biological aspects such as the heterogeneity of tumours and the relapse of many cancers after what appeared to be successful treatments. In the last decade, the first putative breast cancer stem cells were identified and further research was made which strengthened the relevance of the theory. Different markers have been used to identify the breast cancer stem cells and their tumour initiating capacity has been examined both in vitro and in vivo. However, recent studies on the existence and frequency of breast cancer stem cells have had varying results. The interpretation of these results is complicated by the difficulties in establishing a correct micro environment and the different techniques used when separating and identifying the breast cancer stem cells. There is a need for further research on the existence of breast cancer stem cells and their clinical relevance.